THE URGENCY OF VIEWING NON-TEST ASSESSMENTS AS HUMANISTIC ASSESSMENT - Maida Norahmi; Suharyono Suharyono (EnJourMe (English Journal of Merdeka) : Culture, Language, and Teaching of English, 2018)
Assessing students with various characteristics is a challenge for teachers. The effort of being adaptable to each characteristic leads to joyful moments or even frustrating situations. How can we deal with the characteristics? This article is aimed at giving teachers preliminary discussion towards non-test assessments and how urgent they are that teachers should consider in facilitating students’ characteristics. Since syllabus still requires test admission as how to evaluate learning, non-test assessments can take position as students’ supplementary records. Briefly, this article is expected to help teachers cope with their students’ characteristics by supplementing non-test activities in evaluating students’ learning process.